Organizing academic research: The importance of speed in nursing care for early identification of sepsis (Research, Society and Development, 2020)
Introduction: Sepsis is a disease of silent onset, has a great potential for aggravation; therefore, it requires early identification and rapid intervention in order to nullify and / or minimize the risk of hospital mortality of patients admitted to an intensive care unit. Objective to demonstrate the importance of nursing as an actor capable of identifying and intervening early in systemic changes related to sepsis in the ICUs, thus allowing the chance of survival of inpatients. Therefore, bibliographic research, qualitative, descriptive, which demonstrates the role of nursing as the main instrument for early identification of patients affected by sepsis, in addition to describing the main nursing interventions provided in the care of septic patients. With the study, it was concluded that the importance of nurses in the process of early recognition of sepsis is perceived, the technical scientific knowledge of this professional combined with the use of protocols provides quick actions to face the disease, being a differential in the care of septic patients and can help ensure positive outcomes. The nurse is able to identify the onset of sepsis and act according to the institutional protocol, although they demonstrate difficulty in executing this instrument.